Efficacy and Safety of Electro-Thumbtack Needle Therapy for Patients With Chronic Neck Pain: Protocol for a Randomized, Sham-Controlled Trial - Shi, Hangyu; Wang, Xinlu; Yan, Yan; Zhu, Lili; Chen, Yu; Gao, Shuai; Liu, Zhishun (Frontiers in Medicine, 2022)
Background: Chronic neck pain is a prevalent condition adversely impacting patients’ well-being in both life and work experience. Electro-thumbtack needle (ETN) therapy, combining acupuncture with transcutaneous stimulation, might be one of the effective complementary and alternative medicine (CAM) therapies in treating chronic neck pain, although the evidence is scarce. This study aims to estimate the efficacy and safety of ETN therapy for chronic neck pain. Methods and Analysis: This will be a sham-controlled, randomized clinical trial. A total of 180 subjects will be randomly allocated to either the ETN group or the sham ETN group. Treatment will be administrated three times a week for four consecutive weeks, with a 6-month follow-up. The primary outcome measure will be the Numerical Rating Scale for neck pain (NRS-NP) over a period of the four weeks. Secondary outcome measures include the Northwick Park Neck Pain Questionnaire (NPQ), Neck Disability Index (NDI), Patient Global Impression of Change (PGIC), patient expectation and preference assessment. Chi-square test or Fisher’s exact test will be used for proportions of participants having clinically meaningful improvement. Analysis of covariance or repeated-measures analysis of variance will be applied to examine changes in the outcome measures from baseline. Discussions: This prospective trial will contribute to evaluating the efficacy and safety of ETN in the treatment of chronic neck pain, with an intermediate-term follow-up. This study will provide further evidence for clinical neck pain management. Ethics and Dissemination: This trial has been approved by the Research Ethical Committee of Guang’anmen Hospital (ethical approval number: 2021-039-KY-01). Recruitment began in March 2022 and will continue until December 2023. Dissemination plans include posters, WeChat, websites and bulletin boards in hospital and communities. Clinical Trial Registration: This trial is registered at ClinicalTrials.gov (identifier: NCT04981171).